2010
DOI: 10.1093/icb/icq026
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Genetic Variation in Static Allometry in the Threespine Stickleback

Abstract: The common pattern of replicated evolution of a consistent shape-environment relationship might reflect selection acting in similar ways within each environment, but divergently among environments. However, phenotypic evolution depends on the availability of additive genetic variation as well as on the direction of selection, implicating a bias in the distribution of genetic variance as a potential contributor to replicated evolution. Allometry, the relationship between shape and size, is a potential source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…, 2011). And although McGuigan et al. (2010) have shown that evidence of allometry alone does not predict a correlated response to selection between growth/size and body form, it is generally assumed that allometry is ultimately pleiotropic in nature (Klingenberg, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…, 2011). And although McGuigan et al. (2010) have shown that evidence of allometry alone does not predict a correlated response to selection between growth/size and body form, it is generally assumed that allometry is ultimately pleiotropic in nature (Klingenberg, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, available evidence suggests that Rabbit Slough stickleback harbor little to no additive genetic variance in the slope of static allometry (the relationship between size and shape among individuals of the same age; McGuigan et al, 2010b), so additive variance in the slopes of ontogenetic allometry (allometries of individuals of different ages/sizes) is likely not present, since the latter leads to the former (Shingleton et al, 2007). Allometry, and the expression of genetic variance thereof, might be environmentally contingent.…”
Section: Discussionmentioning
confidence: 99%
“…Plastic influences on morphological phenotypes are more apparent in continuously varying characters including body size, body shape and gill raker morphology (Day et al, 1994;Wund et al, 2008McCairns and Bernatchez, 2010, although genetic variation is a primary determinant of variation in expression of these traits (Peichel et al, 2001;Aguirre et al, 2004;Albert et al, 2008;McGuigan et al, 2010;Berner et al, 2014). Factors such as diet, habitat structure, water velocity and salinity vary considerably among populations, and all are known to impact the development of these features in stickleback and/ or other fishes (Day et al, 1994;Pakkasmaa and Piironen, 2000;Imre et al, 2002;McCairns and Bernatchez, 2012;Wund, 2012).…”
Section: Morphological Plasticity In the Radiationmentioning
confidence: 99%